Governança multi-stakeholder na cadeia de valor da carne bovina no Brasil - Schneider, Luis Carlos (Universidade do Vale do Rio dos Sinos, 2016)
Livestock industry is a subject under discussion in Brazil and in the world due to carbon emission, drawing the attention of researchers, activists and other stakeholders. Beef value chain in Brazil is undergoing changes in its governance structure, influenced by institutional environment and stakeholders directly and indirectly related to this chain. There is a move towards private standards and private governance in the global value chains, in which production systems configuration is determined by the leading companies’ performance. Studies about global value chains governance are more related to private standards, from the perspective of the dyadic relations between organizations, and the current approach about global value chains governance leaves a gap when it comes to understanding the influence of stakeholders, such as civil society organizations, NGOs and other nonmarket actors, in value chain governance structures. Few works have highlighted the importance of multi-stakeholder initiatives as an alternative form of creating solutions for complex issues related to private governance in global value chains. Under the perspective of global value chains, the analysis of governance in the beef value chain in Brazil enables highlighting its characteristics, influential factors and forms of interrelation between stakeholders. Through an inductive-deductive investigation, with a qualitative approach, it was possible to analyze the beef value chain, the institutional environment and the relations between stakeholders in order to characterize the governance structure that emerges in this chain. As a result, it can be said that the governance of this chain is dynamic and strongly influenced by the institutional environment, more characterized by the horizontal relations than the vertical ones, and that multi-stakeholder initiatives, identified in two levels in this study, play an important role in this value chain governance structure.
Keywords: Cadeia de valor; Governança; Stakeholders; Multi-stakeholder; Carne Bovina; Value chain; Governance; Beef; ACCNPQ::Ciências Sociais Aplicadas::Administração